Compliance with Fe tablet consumption, pregnancy spacing, frequency of antenatal care, and anemia in pregnant women - Amaral, Pedro; Sumarmi, Sri; Isaura, Emyr Reisha (Universitas Gadjah Mada, 2025)
Purpose: This study aims to determine the effect of compliance with Fe tablet consumption, pregnancy spacing, and frequency of antenatal care (ANC) visits on hemoglobin anemia in pregnant women at the Comoro Community Health Center, Dili, Timor-Leste. Methods: We used discriminant analysis on a randomly selected 84 out of 250 pregnant women. Results: The statistical analysis using discriminant analysis revealed that compliance with Fe tablet consumption (p = 0.00), pregnancy spacing (p = 0.000), and frequency of ANC visits (p = 0.002) all had significance values less than 0.05, indicating that these three factors significantly affect hemoglobin levels in pregnant women with anemia. Conclusion: Compliance with the consumption of Fe tablets was obtained by the “Abnormal” group value, namely a mean or average of 84.31, while the “Normal” group value was a mean or average of 93.29, and the distance between maternal pregnancy and anemia in pregnant women was obtained with the mean or average value of 18.10 (abnormal group) and 23.3 (normal group), so it can show that there is an influence on compliance with the consumption of Fe tablets and the interval between pregnancies and anemia in pregnant women.